The Level of Land Suitability and Analysis of Lemongrass Farming in Krueng Meueh Sub-Watershed Aceh Province (Talenta Publisher, 2020)
Lemongrass is one of the agricultural commodities that produce citronella oil and will be a better product if the cultivation is carried out on the right land in the right way. This study aimed to determine the land suitability classes and farming feasibility for community citronella crops. The research was conducted at the Krueng Meueh Sub-watershed,Â Aceh from April to June 2019. The research was done in descriptive survey methods of forming a land mapping unit (LMU) of the study area. The LMU was obtained from an overlay of a soil map, slope map, and land use map with software ArcGis version 10.1. The soil characteristic data of each LMU and climate data were used for assessing land suitability classes, and to find out the level of farming feasibility of lemongrass in the study area with calculating values of Benefit-Cost Ratio (B/C), Internal Rate of Return (IRR), Net Present Value (NPV) and Break-Even Point (BEP). The result showed that the study area was considered suitable for lemongrass (S2 and S3). Classes of S2 were found at LMU 7 and 17 with base saturation (BS), soil pH, slope, and erosion hazard (EH) as constraint factors. While the other LMU is S3 class with soil pH, BS, organic-C, and EH as a constraint of lemongrass cultivation. The effort of land improvement for lemongrass in the study area such as liming, organic matter, and water-retaining pit or mounds. The lemongrass farming in the study area is feasible and profitable, based on values of NPV Rp.7,076,030, Net B/C 1.2, IRR 16%, and BEP 4 years 4.8 months 24 days. Analysis of Land Suitability andÂ Lemongrass Farming In Krueng Meueh Sub-Watershed Aceh Province Â